Evaluation of quality characteristics of composite cake prepared from mixed jackfruit seed flour and wheat flour (Journal of the Bangladesh Agricultural University, 2017)
In this study, attempt was taken to increase the functionality of cake by substituting wheat flour with 10%, 20%, and 30% jackfruit seed flour (JSF). JSF contained 6.29% moisture, 13.23% protein, 3.09% crude fibre, 73.42% carbohydrates, 2.72% ash and 1.25% fat, and wheat flour contained 12.86% moisture, 1.2% ash, 10.76% protein, 1.32% fat, 1.4% crude fibre and 72.46% carbohydrate. Three cake samples were prepared with composite flour (JSF and wheat flour)mixed with other ingredients and compared with a control sample. The specific volume of cake for 20% substitution was higher than that of all other cakes. The crust and the crumb characteristics changed with the incorporation of JSF. Proximate composition of the cakes like carbohydrate, ash, fibre and protein increased with the substitution of JSF, butfat and protein decreased. Nutritionally, composite cakes with different levels of JSF were found better than control sample. In sensory tests, significant changes were found in color, flavour, texture and taste, and overall acceptability of cakes were observed with the increase of substitution. However, cake with 10% JSF incorporation got the highest acceptability by the panelists.J. Bangladesh Agril. Univ. 14(2): 219-227, December 2016